Caution in the management of SARS‐CoV‐2 infection in males. (5th August 2020) - De Toni, Luca; Garolla, Andrea; Di Nisio, Andrea; Rocca, Maria Santa; Foresta, Carlo
Abstract: The coronavirus 2 (SARS‐CoV‐2) pandemic carries clinical, economic, and social burdens that are currently being disclosed. The key steps of virus life cycle have been recently clarified, highlighting the role of host type 2 angiotensin‐converting enzyme (ACE2) and TMPRSS2 serine protease in virus‐cell binding and entry, respectively. Importantly, major concerns derive from the androgen‐dependent tissue‐expression of both TMPRSS2 and ACE2, suggesting a differential clinical course of the infection between genders. In agreement with this model, available epidemiological data show that the disease in males has an higher risk to display an heavier pattern and associates with both an increased access to critical care unit and higher mortality rate. In this opinion article, available evidence linking the androgen activity with the gender differences observed in SARS‐CoV‐2 infection are discussed, hypothesizing possible therapeutic approaches in male based on the disruption of androgen signaling. On these bases, gender‐specific recommendations for the management of male patients affected by SARS‐CoV‐2 infection are warmly suggested, in order to improve the clinical course of the disease.